2004
DOI: 10.1007/978-3-540-24854-5_53
|View full text |Cite
|
Sign up to set email alerts
|

Automated Extraction of Problem Structure

Abstract: Abstract. Most problems studied in artificial intelligence possess some form of structure, but a precise way to define such structure is so far lacking. We investigate how the notion of problem structure can be made precise, and propose a formal definition of problem structure. The definition is applicable to problems in which the quality of candidate solutions is evaluated by means of a series of tests. This specifies a wide range of problems: tests can be examples in classification, test sequences for a sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…In some cases the objective error of a model approaches infinity, due to some inaccuracy of the model that causes positive or negative feedback. In these cases the model is discarded and the mean objective is calculated using only the remaining well behaved models 5 . Figures 3b and 3c report the mean number of target trials and model evaluations that have been conducted so far, at the end of that particular pass through the estimation phase, respectively.…”
Section: Parametric Identification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the objective error of a model approaches infinity, due to some inaccuracy of the model that causes positive or negative feedback. In these cases the model is discarded and the mean objective is calculated using only the remaining well behaved models 5 . Figures 3b and 3c report the mean number of target trials and model evaluations that have been conducted so far, at the end of that particular pass through the estimation phase, respectively.…”
Section: Parametric Identification Resultsmentioning
confidence: 99%
“…5 A model may be well behaved but still inaccurate 1) Characterization of the target system. The target system is the same as that used in the previous section, the two-eyed monster.…”
Section: Symbolic Identificationmentioning
confidence: 99%
“…Using order theory, Bucci [6,7,8] has deduced that every interactive domain with binary outcomes possesses at least one coordinate system which spans the original domain's Pareto dominance ordering. Each coordinate axis corresponds to a dimension.…”
Section: Preliminariesmentioning
confidence: 99%
“…Recent work [6,7,8] has indicated that within interactive domains, there is an implicit set of yardsticks which might be called informative dimensions. Furthermore, a characterizing property of interactive domains is that they have more than one dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, co-evolutionary algorithms have also been used in structural and architectural design [13,14]. Contrary to conventional evolutionary systems, in which individuals are evaluated using a static quality or fitness metric, co-evolutionary systems consist of one or more populations in which individuals may influence the relative ranking of each other [15]. A new methodology based on co-evolution is presented herein for damage identification using minimal physical testing [11].…”
Section: Introductionmentioning
confidence: 99%